A new critically endangered species of Angraecum (Orchidaceae) endemic to the island of Mauritius, Indian Ocean - Fournel, Jacques; Micheneau, Claire; Baider, Claudia (Phytotaxa, 2015)
Angraecum jeannineanum, a new species endemic to Mauritius, is described and its ecology and conservation status are discussed. Angraecum jeannineanum differs from A. cadetii, which is the morphologically most closely related species, as follows: (i) leaves are smaller, thicker and darker green, (ii) inflorescences and flowers are thinner and smaller, (iii) flowers are more greenish and non-fleshy. Angraecum jeannineanum belongs to Angraecum section Hadrangis, endemic to the Mascarenes, which also includes A. bracteosum, A. cadetii and A. striatum. An updated key for the section is provided. The species should be considered as Critically Endangered (CR) according to the Red List Criteria of the International Union for the Conservation of Nature (IUCN). This assessment is based on the highly restricted species distribution, small population size, and habitat sustaining degradation by invasive alien plants and animals.